Design of Biodegradable Nanoparticles for Oral Delivery of Doxorubicin: In vivo Pharmacokinetics and Toxicity Studies in Rats - Kalaria, D. R; Sharma, G; Beniwal, V; Ravi Kumar, M. N. V (Pharmaceutical research, 2009)
Purpose Doxorubicin, a potent anticancer drug associated with cardiotoxicity and low oral bioavailability, was loaded into nanoparticles with a view to improve its performance. Methods Doxorubicin loaded PLGA nanoparticles were prepared by a double emulsion method. The pH dependent stability of nanoparticles in simulated fluids was evaluated. DSC and XRD studies were carried out in order to ascertain the nature of doxorubicin in formulations in conjunction with accelerated stability studies. The in vitro release was investigated in phosphate buffer. The pharmacokinetic and toxicity studies were conducted in rats. Results Nanoparticles had an average size of 185 nm, with 49% entrapment at 10% w/w of polymer. The particles displayed good pH dependent stability in the pH range 1.1-7.4. DSC and XRD studies revealed the amorphous nature of doxorubicin in nanoparticles and the accelerated stability studies revealed the integrity of formulations. Initial biphasic release (20%) followed by a sustained release (80%) for 24 days was observed under in vitro conditions. The doxorubicin loaded nanoparticles demonstrated superior performance in vivo as evident by enhanced bioavailability and lower toxicity. Conclusions Together, the data indicates the potential of doxorubicin loaded nanoparticles for oral chemotherapy. Further, these formulations could be explored for new indications like leishmaniasis.